2012
DOI: 10.1080/10875549.2011.639862
|View full text |Cite
|
Sign up to set email alerts
|

The Cycle of Social Exclusion for Urban, Young Men of Color in the United States: What Is the Role of Incarceration?

Abstract: This article explores how incarceration amplifies the disconnection from school and work experienced by urban, young men of color in the United States and ultimately leads to their social exclusion. The authors draw on longitudinal data collected in interviews with 397 men age 16 to 18 in a New York City jail and then again one year after their release. Using logistic regression analysis, the authors found that though incarceration did not appear to exacerbate disconnectedness directly, it was associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Based on our contrary findings, we concluded that substance use and constructive outcomes in our sample were more strongly influenced by other factors than by young men’s sense of ethnic pride. For example, in other studies with this sample, drug and alcohol use were related to a clustering of other risk behaviors (Valera et al, 2009), while engagement in constructive outcomes, like employment, were associated with post-jail housing stability (Ramaswamy & Freudenberg, 2012). These findings suggest that the pathways to success for young men leaving jails are complex and layered.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Based on our contrary findings, we concluded that substance use and constructive outcomes in our sample were more strongly influenced by other factors than by young men’s sense of ethnic pride. For example, in other studies with this sample, drug and alcohol use were related to a clustering of other risk behaviors (Valera et al, 2009), while engagement in constructive outcomes, like employment, were associated with post-jail housing stability (Ramaswamy & Freudenberg, 2012). These findings suggest that the pathways to success for young men leaving jails are complex and layered.…”
Section: Discussionmentioning
confidence: 76%
“…More than two million juveniles are arrested every year. In 2006, 85% of all incarcerated juveniles were male (Child Trends, 2010); 70% of these young offenders were males of color (Ramaswamy & Freudenberg, 2012), even though men of color make up only 22% of the total U.S. population. In 2006, the detention rates were more than 5 times higher among Black youth and 2 times higher among Latino youth when compared with White individuals of the same age group (Hartney & Vuong, 2009), and the majority of those young Black and Latino men came from low-income families (Daniels, Crum, Ramaswamy, & Freudenberg, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kicks inferred that high transfer rates are due to Black male youth who "make the wrong choice with that wrong person." These wrong choices Kicks referred to can also be understood as learned behaviors from the sociocultural conditions outside the school system that lack adequate social-emotional, mental, and economic support for families, particularly in urban communities (Ramaswamy & Freudenberg, 2012). Though Bottoms' and Kicks' disagree about the relation between having peers at UBA and its direct relation to high transfer rates for Black males, both participants' responses suggest Black male youth are individuals, and their experiences should be perceived and treated as such.…”
Section: Introductionmentioning
confidence: 99%